Consumer motives for purchasing organic coffee. Issue 6 (10th August 2015) - Lee, Kyung Hee; Bonn, Mark A.; Cho, Meehee
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This study aims to investigate consumer choice motives for purchasing organic coffee by applying the Theory of Planned Behavior (TPB) approach and how those are influenced by different degrees of ethical concern and price sensitivity to gain a better understanding about consumer behavior related to the rapidly growing demand for this unique product. Design/methodology/approach – Data were collected from consumers at cafés (n = 482) located in seven metropolitan cities in South Korea using a self-administered questionnaire. Data were analyzed using descriptive statistics, confirmatory factor analysis and structural equation modeling. Findings – Results documented that health and environmental protection were predictors of purchase attitude and subjective norm. Environmental protection was found to be a predictor of perceived behavioral control. TPB antecedents were significantly related to purchase intention. Ethical concern and price sensitivity documented the significant moderating roles upon organic coffee purchasing behavior. Research limitations/implications – Findings further contribute to a better understanding about influential choice motives regarding organic coffee and their effect upon consumer purchase behavior. Practical implications – Findings assist in understanding the roles ethical concerns and price sensitivity play upon consumer behavior issues specific to purchasing organic coffee. New research findings assist with marketing and promoting the social benefits associated with organic coffee while also offering pricing strategies for café and restaurant businesses to optimize their organic coffee sales revenue potential. Originality/value – This study is one of the first to clarify consumer motives for purchasing organic coffee, and to ascertain whether consumer purchase attitudes and intentions regarding organic coffee are influenced by different degrees of ethical concern and price sensitivity.